A Study on the Stability of Water-Gated Organic Field-Effect-Transistors Based on a Commercial p-Type Polymer - Picca, Rosaria Anna; Manoli, Kyriaki; Macchia, Eleonora; Tricase, Angelo; Di Franco, Cinzia; Scamarcio, Gaetano; Cioffi, Nicola; Torsi, Luisa (Frontiers in Chemistry, 2019)
Robust electrolyte-gated organic field-effect-transistors (OFETs) are particularly needed for the development of biosensing devices. However, when a FET biosensor operates in aqueous environments or even in real biological fluids, some critical issues may arise due to the possible lack of environmental long-term and/or operational stability. An important source of instability is associated with the degradation of the organic electronic channel materials such as for instance, poly-3-hexylthiophene (P3HT), a benchmark commercially available p-type organic semiconductor. In this work, the investigation of critical parameters, such as the control over spurious electrochemical phenomena as well as the operating conditions that can affect water-gated OFETs lifetime, is reported, together with a proposed modeling of the P3HT stability curve over one week in water. The investigation of possible morphological/chemical modifications occurring at the polymer surface after operating in water for two weeks was carried out. Moreover, it is proven how the addition of a gel layer can extend the P3HT based water-gated OFET shelf life up to two months.